Clouds of words as a didactic tool in literary education of primary school children - Liudmyla L. Nezhyva; Svitlana P. Palamar; Maiia V. Marienko (Academy of Cognitive and Natural Sciences, 2022)
The study reveals the possibilities of using the words' cloud in the literary education of primary school children. The authors consider the possibility of using a cloud of words to visualize the keywords of the text for the translation of the work of art, the interpretation of the main idea and the characteristics of the artistic image. The words' cloud can also be used as a reference summary to answer questions about the content of the work or to present the results of a school project by students. Moreover, in reading lessons, this tool can be used as a tool to identify the topic of the lesson. The study reveals the possibilities of the didactic tool of the words' cloud for the development of speech of primary school children, in particular, in composing their own texts and editing them, the ability to explore words that the student uses too often and avoid tautology. Using the method of a problem situation and visually demonstrating information through a cloud of words, the teacher pro-motes the activation of students' mental activity, the development of creative abilities and critical thinking. The study tested the use of the electronic resource WordArt in primary school - a website for creating a "word's cloud" and proved its effectiveness in reflection, as well as creating an image of the main idea of the lesson, general conversation, its use as didactic material. The authors used the technology of learning using a cloud office package Google Drive to write a draft of their own statement of primary school children. The authors investigated the use of the service in the lesson of literary reading during the organization of reading activities in the following areas: in the "cloud of words" to encrypt the topic of the lesson; using the cloud as visual material or as basic information to explain new material; encrypt certain words from the text in the cloud, students' task to guess the work; create a cloud of words of positive and negative characters of the work; write a story on the topic; create an "encrypted postcard" to the writer or hero of the work. In the course of experimental work, the effectiveness of the use of this didactic tool in the lessons of literary reading in primary school during the analysis of texts in order to identify the most important associations of students was confirmed.